Hubungan Motivasi Belajar dengan Hasil Belajar Siswa Kelas X dalam Mengikuti Pembelajaran PJOK - Chrisabel Anatasya Miradita; Mochamad Ridwan; Muhamad Thurham; Alif Hanifah (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Students' intrinsic drive to learn and their performance in PJOK (Physical Education, Sports, and Health) courses in tenth grade are the subjects of this research. Using a correlational strategy, the research takes a quantitative approach. A total of 395 students from SMA Negeri 1 Driyorejo make up the population. Using a cluster sampling approach, 70 students were chosen from 11 classes to make up the sample. Data on learning outcomes were derived from students' PJOK scores, and the study instrument was a learning motivation questionnaire that has been validated and demonstrated to be accurate in prior investigations. Because the variables did not follow a normal distribution, descriptive statistics were used to find out how the data was distributed, and inferential statistics were used to draw conclusions based on the data using Spearman rank correlation. C=0.520 (p>0.05) is the correlation coefficient that the data demonstrate. Based on these results, it seems that students' learning outcomes are unrelated to their desire to study. This provides further evidence that variables other than learning motivation, such as motor abilities and instructional strategies, impact PJOK learning results.